Bank Performance with CAMELS Ratios towards earnings management practices In State Banks and Private Banks - Salhuteru, Fentje; Wattimena, Fransina (Advances in Social Sciences Research Journal, 2015)
This study aimed to examine the influence of CAMELS ratio toward earnings management practices in state bank limited to PT Bank Negara Indonesia(Persero ), PT Bank BTN ( Persero),PT Bank Central Asia Tbkdan PT Bank ArthaGraha. This study used secondary data of monthly financial report of the state bank published by Bank Indonesia during 2012 and 2013. The sampling technique used are purposive sampling with the sample from 18 months of bank financial statements. Earnings management are proxy by discretionary accruals that have been adapted to the characteristics of banking . Determination of the coefficient of earnings management was done by regressing total accruals which was calculated with the model Healy and Jones. Testing the influence of the earnings management and the effect of CAMELS ratio towards earnings management was done using the multiple regression. During research period show as variable and data research was normally distributed. Based on test, multicolinearity test, heterosskedasticity test and auto correlation test classic assumption deviation has no founded, this indicate that the available data has fulfill the condition to use multi linear regression model.This result of research shows to Governtment Bank,Variable NPM, positive significant influence toward earnings management. Ratio CAR and MR negative not significant influence,RORA,ROA,LDR positive not significant toward earnings management. to Private Bank,Variable ROA,NPM, positive significant influence toward earnings management. Ratio CAR and LDR negative not significant influence,RORA and MR positive not significant toward earnings management.